Activation and reactivity of epoxides on solid acid catalysts - Saikia, Lakshi; Satyarthi, J. K.; Srinivas, Darbha; Ratnasamy, P. (Journal of Catalysis, 2007)
The aminolysis of epoxides over novel solid catalysts (Bronsted-acidic SBA-15 functionalized with propylsulfonic acid and Lewis-acidic Ti-MCM-41) is reported. The acidic properties of these catalysts were determined by FTIR spectroscopy and temperature-programmed desorption of pyridine and NH3, respectively. The mesoporous solid acids of the present study are reusable and exhibit significantly higher catalytic activities than known catalysts for opening of the oxirane ring with nitrogen (aromatic and aliphatic amines)-containing and oxygen (alcohols)-containing nucleophiles. A range of beta-amino, alcohols with high regioselectivity and stereoselectivity were synthesized. Adsorption studies as well as the sigmoid shape of the conversion- versus-time plots show that the epoxide and amine compete for adsorption on the acidic sites (-SO3H or Ti4+) on the catalyst surface. Epoxide adsorption and activation on acid sites are the more critical processes. Catalytic activity decreases with increasing basicity of the amines and/or the alcohol, as well as the dielectric constant of the solvent. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: aminolysis and alcoholysis of epoxides; beta-Amino alcohols; ring opening of epoxides; SBA-15 functionalized with propylsulfortic acid; Solid acids; Ti-MCM-41

Active sites in vanadia/titania catalysts for selective aerial oxidation of beta-picoline to nicotinic acid - Srinivas, Darbha; Hoelderich, Wolfgang F.; Kujath, Steffen; Valkenberg, Michael H.; Raja, Thirumalaiswamy; Saikia, Lakshi; Hinze, Ramona; Ramaswamy, Veda (Journal of Catalysis, 2008)
Vanadia/titania catalysts with varying vanadium content were prepared by impregnation using three different titania carrier materials of varying surface area, The structure of active vanadium species for beta-picoline oxidation was investigated. Vanadium is mainly in the +5 oxidation state as revealed by electron paramagnetic resonance (EPR) and V-51 magic-angle spinning nuclear magnetic resonance (V-51 MAS NMR) spectroscopy techniques. Diffuse reflectance UV-visible (DRUV-vis) spectroscopy and spectral deconvolution enabled identification of at least five different types of vanadium oxide species in these catalysts: monomeric tetrahedral VO43-, polymeric distorted tetrahedral VO3-, square pyramidal V2O5, octahedral V2O62- and V4+ oxide species. While both VO43- and VO3- species are active in beta-picoline oxidation, the latter having a distorted tetrahedral geometry yielded the desired products-picolinaldehyde and nicotinic acid. High surface area, anatase structure for the support and dispersed, distorted tetrahedral vanadium oxide species are the key parameters determining the activity and selectivity of these oxidation catalysts. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Active vanadium species; Nicotinic acid; Oxidation of beta-picoline; Selective aerial oxidation; Spectroscopic investigations; Vanadia/titania